Improving elementary school students’ self-regulated learning through growth mindset psychoeducation - Alexander, Angelita Asafani; Rohinsa, Meilani; Megarini, M. Yuni (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study examines the effectiveness of growth mindset psychoeducation using a quasi-experimental one-group pretest-posttest design involving 18 sixth-grade students at